2018
DOI: 10.3126/jnhrc.v15i3.18851
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Caregiver Burden in Caregivers of Patients with Schizophrenia and Bipolar Affective Disorder in Kathmandu Medical College

Abstract: 258Background: Schizophrenia and bipolar affective disorder are chronic psychiatric illness that requires long term care. This study tends to measure psychological burden and factors associated with it among caregivers of these two illnesses.Methods: This is a cross-sectional study that included participants by purposive sampling method. Self designed performa was used to collect the socio-demographic details of the caregivers. Modified caregiver strain index was used to assess the overall stress. Beck`s depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 14 publications
3
37
0
Order By: Relevance
“…Concerning women, covariates including health problems, division of care and time in care activity were also associated with the manifestation of burden. These covariates have demonstrated an association with burden in previous studies conducted with caregiver populations where men and women were jointly analysed (Demarco et al, 2015; Sharma et al, 2018; Souza et al, 2017). However, the findings of this study suggest that, in our sample, several factors differ for male versus female caregivers.…”
Section: Discussionmentioning
confidence: 92%
“…Concerning women, covariates including health problems, division of care and time in care activity were also associated with the manifestation of burden. These covariates have demonstrated an association with burden in previous studies conducted with caregiver populations where men and women were jointly analysed (Demarco et al, 2015; Sharma et al, 2018; Souza et al, 2017). However, the findings of this study suggest that, in our sample, several factors differ for male versus female caregivers.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, this review examines the characteristics and culture background of participants reported by the studies. Table 2 indicates that, in terms of the geographic location of the studies, 33.33% were conducted with participants from rural locations (Kaufman, 2015 ; Shidhaye et al, 2016 ; Maselko et al, 2018 ), 33.33% were conducted with participants from rural and non-rural locations (Mathias et al, 2015 ; Lee et al, 2016 ; Seponski et al, 2018 ), 11.11% were conducted with participants from non-rural locations only (Xu et al, 2015 ), and 22.22% did not report the geographical location the participant was recruited from (Manning et al, 2015 ; Sharma et al, 2018 ). In terms of income status, only 33.33% of the found manuscripts provide information on the participant's income status and majority of the participants are of middle- to low-income groups (Kaufman, 2015 ; Lee et al, 2016 ; Shidhaye et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of income status, only 33.33% of the found manuscripts provide information on the participant's income status and majority of the participants are of middle- to low-income groups (Kaufman, 2015 ; Lee et al, 2016 ; Shidhaye et al, 2016 ). In terms of education status, 100% of the manuscripts provided information on the participants' education status (Kaufman, 2015 ; Manning et al, 2015 ; Mathias et al, 2015 ; Xu et al, 2015 ; Lee et al, 2016 ; Shidhaye et al, 2016 ; Maselko et al, 2018 ; Seponski et al, 2018 ; Sharma et al, 2018 ). Majority of the participants are of low education status.…”
Section: Resultsmentioning
confidence: 99%
“…Families, as primary caregivers, are often overwhelmed by the uncontrolled behavior of schizophrenia patients (Mantovani et al, 2016). Research conducted by Sharma et al (2017) stated that 72% of families had high-stress levels, 25% had depression, and 29% had anxiety related to the treatment of schizophrenia patients. Some of the effects of the burden of care include mental health problems (e.g., depression, anxiety, stress, and fatigue), decreased physical health (e.g.…”
Section: Discussionmentioning
confidence: 99%